Epidemiological Profile of Vitamin D Deficency Among Hypertensive Patients - Suman Kotwal; Vishal R Tandon; Annil Mahajan; Sana Bashir; Irtiqa Ayani Rathore; Sajid Alam (Dr. Annil Mahajan, 2024)
Background: Vitamin D deficiency is a worldwide epidemic health problem. Variable results are available with few studies favouring and others denying the association of Vit D deficiency and Hypertension. Material and Methods: An Epidemiological prospective Cross-sectional 3 year observational study was conducted to determine the point prevalence of vitamin D deficiency among hypertensive patients in comparison to age , sex matched, healthy controls among urban and rural population of the Jammu region and also to evaluate the correlation between vitamin D deficiency and hypertension.Group1 ( n = 856) patients of Hypertension with any co-morbid profile with or without complications presenting in tertiary care Medical college. Group 2 (n= 1006) healthy subjects. Results: The study included 1862 patients (856 cases and 1006 controls) with male-to-female ratios of 1.62:1 and 1.13:1, respectively, Prevalence rates of vitamin D sufficiency (>30 ng/mL), insufficiency (20-30 ng/mL), and the deficiency (<20 ng/mL) were 21.2%, 21.3%, and 57.3% in hypertensive, and 19.7%, 19.3%, and 60.8% in non-hypertensive, respectively. The Mantel-Haenszel Chi-Square test (MH Chi-Sq. value = 2.345, CI=95%, p = 0.309) indicated no significant linear trend between vitamin D levels and hypertension. Conclusion: Despite notable high prevalence rates of Vitamin D deficiency both in hypertensive arm (78.7%) and healthy control arm (80.2%) in the study population, this study found no significant association between Vitamin D levels and hypertension